Social Panorama of Latin America 2006 - United Nations (United Nations, 2007)
In the last four years, Latin America has turned in its best performance in twenty-five years in economic and social terms. Progress with poverty reduction, falling unemployment, improving income distribution in several countries and a strong upswing in numbers of jobs are the main factors underlying the positive trend in a number of the region's countries. The first two chapters of in this report look at the way the main social indicators have behaved in the last few years. The following two chapters address matters that, for different reasons, have come to figure prominently on government agendas.